The Development of Biogas Production in the Context of Energy Transition: The Case of Poland - Szterlik, Paulina (Journal of Public Governance, 2021)
Objective: The aim of this article is to identify the chances of further development of biogas production as a way to diverisfy the structure of energy production in Poland. Another one is to analyse biogas production as a part of getting closer to achieving the targets of the climate and energy framework of the European Union and Polish long-term energy sector strategies. Research Design & Methods: The research methods used in the study include: the analysis and study of the literature, heuristic techniques for data analysis, the SWOT (strengths, weaknesses, opportunities, threats) analysis. Findings: The production of biogas can be beneficial for local economic growth, environmental awareness, and social wellbeing. There is a strong need to overcome the barriers of further development of biogas production as well as analyse the opportunities, given that a type of renewable energy source is further developed. Biogas production can help meet the national and international goals concerning energy transition, developing low-carbon economies, and addressing modern economic trends. Implications / Recommendations: The aim of this paper is to investigate the chances of further development of biogas production in spite of current changes in Polish agendas. The topic is of great importance when analysing the strategy of Poland to develop a low-carbon economy. It is also a significant part of current discussions between the scientific community and business practitioners in terms of energy transition in Poland. What is worth noting is that Polish strategies concerning the development of renewable energy production should be aligned with the climate and energy targets of the European Union, which can prove problematic. Polish energy mix is still based on energy production from coal, while the EU is steadily increasing gross energy production from renewable energy sources. Contribution / Value Added: The analysis defines the role of biogas in circular economy as well as in modern economy with the consideration of environmental economics and sustainable development. It underlines the importance of biogas in energy transition in Poland, taking into consideration the Energy Policy of Poland until 2040 (Pol. Polityka energetyczna Polski do 2040 r.)